Motivasi, Disiplin, Dan Insentif Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Tulungagung - Rahayu, Puji; Rusandy, Deby Santyo (Otonomi, 2025)
Human resources are one of the most vital elements for organizations or government agencies. Because their role in implementing strategies is very important, namely as the subject of implementing organizational strategies. This study aims to: (1) Analyze motivation partially influencing employee performance at the Public Works and Spatial Planning Agency of Tulungagung Regency. (2) Analyze discipline partially influencing employee performance at the Public Works and Spatial Planning Agency of Tulungagung Regency. (3) Analyze incentives partially influencing employee performance at the Public Works and Spatial Planning Agency of Tulungagung Regency. (4) Analyze motivation, discipline, and incentives simultaneously influencing employee performance at the Public Works and Spatial Planning Agency of Tulungagung Regency. (5) Analyze the most dominant motivation, discipline, and incentive variables on employee performance at the Public Works and Spatial Planning Agency of Tulungagung Regency. This study uses a quantitative analysis method, namely analysis of data that has been scored according to the measurement scale that has been set using statistical formulas. The analysis used is for data in the form of numbers. While the quality test uses (1) Descriptive statistical analysis, (2) Verification analysis. (3) Classical assumption test (4) Multiple regression analysis, and (5) Hypothesis testing, (6) Determination Coefficient Analysis (R2). The results of the study show that: (1) Motivation partially has a significant influence on employee performance at the Public Works and Spatial Planning Service of Tulungagung Regency. (2) Discipline partially has a significant influence on employee performance at the Public Works and Spatial Planning Service of Tulungagung Regency. (3) Incentives partially have a significant influence on employee performance at the Public Works and Spatial Planning Service of Tulungagung Regency. (4) Motivation, discipline, and incentives simultaneously have a significant influence on civil performance at the Public Works and Spatial Planning Service of Tulungagung Regency. (5) Motivation has the most dominant influence on employee performance at the Public Works and Spatial Planning Service of Tulungagung Regency